Measuring the level of job performance of kindergarten teachers in terms of competence (professional, educational, personal, social) in the city of Makkah - Alluhaybi, Shaymah Dakhel (Journal of Educational and Psychological Sciences, 2025)
The study aimed to measure the level of job performance of kindergarten teachers in terms of competence (professional, educational, personal, social) in Makkah. The research also aimed to identify statistically significant differences between the responses of the study sample according to the variable (Educational qualification, years of experience). The study relied on the descriptive approach, and to measure the level of job performance of kindergarten teachers in Makkah, the study tool (questionnaire) was built, which consisted of two parts: the first part includes preliminary data on the study sample members according to the study variables. The second part is the questionnaire, which includes (24) points. The study tool was applied to a sample of kindergarten teachers in Makkah, which consisted of (221) teachers from kindergarten schools in Makkah. Among the most important results of the study: The response of the study sample confirmed about the level of kindergarten teachers’ job performance with a general average that reflects (a large degree) in all dimensions of job performance with mean of (4.25); Where Personal competence came in the first place with mean of (4.27), which means that teachers' awareness of the importance of professional commitment, In the second order came Professional competence with mean of (4.26); and in the third order came Social competence with an mean of (4.26); and in the fourth order came Educational competence with mean of (4.22(; which means that kindergarten teachers have ability of developing the educational process in school.
Keywords: Educational competence; job performance; kindergarten; Personal competence; Professional competence; Social competence